A self-controllable voltage level (SVL) circuit and its low-power high-speed CMOS circuit applications. - Enomoto, T. (IEEE Journal of solid state circuits)
A self-controllable voltage level (SVL) circuit which can supply a maximum dc voltage to an active-load circuit on request or can decrease the dc voltage supplied to a load circuit in standby mode was developed. This SVL circuit can drastically reduce standby leakage power of CMOS logic circuits with minimal overheads in terms of chip area and speed. Furthermore, it can also be applied to memories and registers, because such circuits fitted with SVL circuits can retain data even in the standby mode. The standby power of an 8-bit 0.13-μm CMOS ripple carry adder (RCA) with an on-chip SVL circuit is 8.2 nW, namely, 4.0% of that of an equivalent conventional adder, while the output signal delay is 786 ps, namely, only 2.3% longer than that of the equivalent conventional adder. Moreover, the standby power of a 512-bit memory cell array incorporating an SVL circuit for a 0.13-μm 512-bit SRAM is 69.1 nW, which is 3.9% of that of an equivalent conventional memory-cell array. The read-access time of this 0.13-μm SRAM is 285 ps, that is, only 2 ps slower than that of the equivalent SRAM.